Estimated substitution of tea or coffee for sugar-sweetened beverages was associated with lower type 2 diabetes incidence in case–cohort analysis across 8 European countries in the EPIC-interact study - Imamura, F; Schulze, MB; Sharp, SJ; Guevara, M; Romaguera, D; Bendinelli, B; Salamanca-Fernández, E; Ardanaz, E; Arriola, L; Aune, D; Boeing, H; Dow, C; et al. (Oxford University Press, 2019)
Introduction Beverage consumption is a modifiable risk factor for type 2 diabetes (T2D), but there is insufficient evidence to inform the suitability of substituting 1 type of beverage for another. Objective The aim of this study was to estimate the risk of T2D when consumption of sugar-sweetened beverages (SSBs) was replaced with consumption of fruit juice, milk, coffee, or tea. Methods In the European Prospective Investigation into Cancer and Nutrition (EPIC)–InterAct case–cohort study of 8 European countries (n = 27,662, with 12,333 cases of incident T2D, 1992–2007), beverage consumption was estimated at baseline by dietary questionnaires. Using Prentice-weighted Cox regression adjusting for other beverages and potential confounders, we estimated associations of substituting 1 type of beverage for another on incident T2D. Results Mean ± SD of estimated consumption of SSB was 55 ± 105 g/d. Means ± SDs for the other beverages were as follows: fruit juice, 59 ± 101 g/d; milk, 209 ± 203 g/d; coffee, 381 ± 372 g/d; and tea, 152 ± 282 g/d. Substituting coffee for SSBs by 250 g/d was associated with a 21% lower incidence of T2D (95% CI: 12%, 29%). The rate difference was −12.0 (95% CI: −20.0, −5.0) per 10,000 person-years among adults consuming SSBs ≥250 g/d (absolute rate = 48.3/10,000). Substituting tea for SSBs was estimated to lower T2D incidence by 22% (95% CI: 15%, 28%) or −11.0 (95% CI: −20.0, −2.6) per 10,000 person-years, whereas substituting fruit juice or milk was estimated not to alter T2D risk significantly. Conclusions These findings indicate a potential benefit of substituting coffee or tea for SSBs for the primary prevention of T2D and may help formulate public health recommendations on beverage consumption in different populations.